Nanomedicine for the treatment of Alzheimer's disease. (April 2015) - Gregori, Maria; Masserini, Massimo; Mancini, Simona
Alzheimer's disease affects more than 35 million people worldwide and this number is presumed to double by the year 2050. Currently, there is no efficient therapy for this disorder but a promising approach is represented by nanotechnology, easily multifunctionalizable devices with size in the order of billionth of meter. This review provides a concise survey on the nano-based strategies for Alzheimer's disease treatment, aiming at carrying drugs across the blood–brain barrier, in particular to target the metabolism of β-amyloid peptide, a pivotal player in this pathology.